Number needed to freeze: cumulative live birth rate after fertility preservation in women with endometriosis. Issue 4 (April 2021) - Cobo, Ana; Coello, Aila; de los Santos, María José; Giles, Juan; Pellicer, Antonio; Remohí, José; García-Velasco, Juan A.
Abstract: Research question: How does the number of oocytes used affect the cumulative live birth rate (CLBR) in endometriosis patients who had their oocytes vitrified for fertility preservation? Design: Retrospective observational study including data from 485 women with endometriosis who underwent fertility preservation from January 2007 to July 2018. Survival curves and Kaplan–Meier plots were used to analyse the CLBR according to the number of vitrified oocytes used. Endometriosis curves were compared with plots developed using elective fertility preservation (EFP) patients as control group. Log-rank, Breslow and Tarone–Ware tests were used to compare the survival curves. Results: The CLBR increased as the number of oocytes used per patient rose, reaching 89.5% (95% confidence interval [CI] 80.0–99.1%) using 22 oocytes. Higher outcomes were observed in young women (≤35 years old versus >35 years old). In the younger group, the CLBR was 95.4% (95% CI 87.2–103.6%) using approximately 20 oocytes versus 79.6% (95% CI 58.1–101.1%) in older women (log-rank [Mantel–Cox] P  = 0.002). The mean age was higher in EFP patients (37.2 ± 4.9 versus 35.7 ± 3.7; P  < 0.001). The outcome was better in the endometriosis group as compared with EFP: a CLBR of 89.5% (95% CI 80.0–99.1%) versus 59.9% (95% CI 51.4–68.6%) when 22 oocytes were used (log-rank [Mantel–Cox] P  < 0.00001). Conclusion: The probability of live birth increases as the number of oocytes used increases in patients with endometriosis, but better outcomes were observed among young women. The information provided here may be of interest to both patients and treating physicians for counselling purposes.